2018
DOI: 10.1111/wrr.12680
|View full text |Cite
|
Sign up to set email alerts
|

Visualized identification of the maximal surgical delay effect in a rat flap model

Abstract: Currently, experimental evidence suggests that the surgical delay can increase flap survival area, but its effect may decrease if the optimal delay period is missed. The aim of this study is to establish a sensitive and objective modality based on the visualized and individualized infrared thermography for identifying the maximal surgical delay effect. A rectangular three‐angiosome flap was designed on the unilateral dorsum of the rat. Ninety‐six rats were randomly divided into six groups according to the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…From the three imaging methods tested, the indocyanine green angiography was shown to be the most precise. The advantages of the infrared thermography such as its noninvasive use have been already shown in other studies [13]. In contrast to the study of Li et al; infrared thermography was shown not to reproduce evaluable results in our study.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…From the three imaging methods tested, the indocyanine green angiography was shown to be the most precise. The advantages of the infrared thermography such as its noninvasive use have been already shown in other studies [13]. In contrast to the study of Li et al; infrared thermography was shown not to reproduce evaluable results in our study.…”
Section: Discussioncontrasting
confidence: 97%
“…To determine tissue perfusion, different imaging modalities have been tested, such as laser Doppler flowmetry for cutaneous circulation [12], infrared thermography [13], indocyanine green angiography [1,14] and near-infrared reflectance-based imaging [15]. While these devices may eventually predict the malperfusion accurately, there might be differences in their features such as application handling and invasivity.…”
Section: Introductionmentioning
confidence: 99%
“…There are 3 angiosomes in the right dorsum of Sprague-Dawley rats. These are, from the caudal side to the cranial side of the rat, the ILAV, the PIAV, and the TDAV, [14][15][16] designated as angiosomes I, II, and III, respectively. The anastomosis between angiosomes I and II was termed choke 1, and the anastomosis between angiosomes II and III was described as choke 2.…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%
“…Finally, the most distinct and significant morphological alteration is the vascular changes, such as the choke vessels dilation and neovascularization 3 . Our previous studies demonstrated that the maximum survival area after perforator flap elevation is mainly achieved through the vasodilation and angiogenesis, and the flap is characterised by a first increase and then decrease in temperature over time 5,6 . Mao et al 7 reported that blood flow, vascular diameters, and microvascular count are clearly increased after flap elevation, and vascular changes are closely associated with the shear stress caused by the increased blood perfusion after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…3 Our previous studies demonstrated that the maximum survival area after perforator flap elevation is mainly achieved through the vasodilation and angiogenesis, and the flap is characterised by a first increase and then decrease in temperature over time. 5,6 Mao et al 7 reported that blood flow, vascular diameters, and microvascular count are clearly increased after flap elevation, and vascular changes are closely associated with the shear stress caused by the increased blood perfusion after surgery. Previous studies indicated that shear stress can activate some mechanosensors situated on the endothelial cell (EC) membrane to trigger several acute signalling pathways, including the synthesis of nitric oxide (NO) by endothelial NO synthase (eNOS) or release of endothelial-derived hyperpolarisation factor, ultimately increasing the vasodilation.…”
mentioning
confidence: 99%